13C15N: glucagon-based novel isotope dilution mass spectrometry method for measurement of glucagon metabolism in humans - Renuse, Santosh; Benson, Linda M.; Vanderboom, Patrick M.; Ruchi, F. N. U.; Yadav, Yogesh R.; Johnson, Kenneth L.; Brown, Benjamin C.; Peterson, Jane A.; Basu, Rita; McCormick, Daniel J.; Pandey, Akhilesh; Basu, Ananda (Clinical proteomics, 2022)
Background Glucagon serves as an important regulatory hormone for regulating blood glucose concentration with tight feedback control exerted by insulin and glucose. There are critical gaps in our understanding of glucagon kinetics, pancreatic α cell function and intra-islet feedback network that are disrupted in type 1 diabetes. This is important for translational research applications of evolving dual-hormone (insulin + glucagon) closed-loop artificial pancreas algorithms and their usage in type 1 diabetes. Thus, it is important to accurately measure glucagon kinetics in vivo and to develop robust models of glucose-insulin-glucagon interplay that could inform next generation of artificial pancreas algorithms. Methods Here, we describe the administration of novel 13 C 15 N heavy isotope-containing glucagon tracers—FF glucagon [(Phe 6 13 C 9 , 15 N; Phe 22 13 C 9 , 15 N)] and FFLA glucagon [(Phe 6 13 C 9 , 15 N; Phe 22 13 C 9 , 15 N; Leu 14 13 C 6 , 15 N; Ala 19 13 C 3 )] followed by anti-glucagon antibody-based enrichment and LC–MS/MS based-targeted assays using high-resolution mass spectrometry to determine levels of infused glucagon in plasma samples. The optimized assay results were applied for measurement of glucagon turnover in subjects with and without type 1 diabetes infused with isotopically labeled glucagon tracers. Results The limit of quantitation was found to be 1.56 pg/ml using stable isotope-labeled glucagon as an internal standard. Intra and inter-assay variability was < 6% and < 16%, respectively, for FF glucagon while it was < 5% and < 23%, respectively, for FFLA glucagon. Further, we carried out a novel isotope dilution technique using glucagon tracers for studying glucagon kinetics in type 1 diabetes. Conclusions The methods described in this study for simultaneous detection and quantitation of glucagon tracers have clinical utility for investigating glucagon kinetics in vivo in humans.